Balete world a Filipino mythological theme park bridging the past and present through landscape design and frontier technology - Baria, Justine Ian E. (College of Architecture, University of the Philippines Diliman, 2019)
The narratives of Filipinos through Philippine Lower Mythology are rich and full of meaning. They hold a lot of potential in providing edutainment experiences in recreational landscape developments. This study primarily explores the typologies of the creatures of Philippine Lower Mythology and associates them to narrative landscape techniques, in order to come up with a theme park development proposal for the country. By exploring theme park trends, environmental psychology, experiential design and narrative landscapes, the study bridges the past and present through a design proposal that uses folklore and frontier technologies as platforms for instilling Filipino culture to the current generations.